Enhanced dark fermentative biohydrogen production from marine macroalgae Padina tetrastromatica by different pretreatment processes - M. Radha; A.G. Murugesan (Biofuel Research Journal, 2017)
Marine macroalgae are promising substrates for biofuel production. Pretreating macroalgae with chemicals could remove microbial inhibitors and enhance the accessibility of the microorganisms involved in the process to the substrates leading to increased product yield. In the present study, Padina tetrastromatica a seaweed species was subjected to different chemical pretreatment in order to remove phenolic content and to enhance biohydrogen production. Different mineral acids (i.e., HCl, H2SO4, and HNO3) and bases (NaOH and KOH) were applied for effective pretreatment of the seaweed. Dilute sulphuric acid treatment of seaweed resulted in the highest cumulative biohydrogen production of 78 ± 2.9 mL/0.05 g VS and reduced phenolic content to 1.6 ±0.072 mg gallic acid equivalent (GAE)/g. Optimization of three variables for pretreatment (i.e., substrate concentration, acid concentration, and reaction time) was examined by Response Surface Methodology. After the optimization of the pretreatment conditions, phenolic content was decreased to 0.06 mg GAE/g. and enhanced biohydrogen production was observed. Structural changes due to pretreatment was studied by FTIR and XRD analyses. The results clearly indicated that the dilute sulphuric acid pretreatment was effective in removing phenolic content and enhancing biohydrogen production.